Combining multi-isotopic and molecular source tracking methods to identify nitrate pollution sources in surface and groundwater. (1st January 2021) - Carrey, Raúl; Ballesté, Elisenda; Blanch, Anicet R.; Lucena, Francisco; Pons, Pere; López, Juan Manuel; Rull, Marina; Solà, Joan; Micola, Nuria; Fraile, Josep; Garrido, Teresa; Munné, Antoni; et al.
Highlights: Multi-isotopic and molecular source tracking data show high agreement to identify nitrate sources. ẟ 11 B in effluents of wastewater treatment plant can be affected by livestock wastes. Information obtained was employed by local authorities to establish new vulnerable zones. Abstract: Nitrate (NO3 - ) pollution adversely impacts surface and groundwater quality. In recent decades, many countries have implemented measures to control and reduce anthropogenic nitrate pollution in water resources. However, to effectively implement mitigation measures at the origin of pollution, the source of nitrate must first be identified. The stable nitrogen and oxygen isotopes of NO3 - ( ẟ 15 N and ẟ 18 O) have been widely used to identify NO3 - sources in water, and their combination with other stable isotopes such as boron ( ẟ 11 B) has further improved nitrate source identification. However, the use of these datasets has been limited due to their overlapping isotopic ranges, mixing between sources, and/or isotopic fractionation related to physicochemical processes. To overcome these limitations, we combined a multi-isotopic analysis with fecal indicator bacteria (FIB) and microbial source tracking (MST) techniques to improve nitrate origin identification. We applied this novel approach on 149 groundwater and 39 surface water samples distributed across Catalonia (NE Spain). A further 18 wastewater treatment plant (WWTP) effluents were also isotopically and biologically characterized. The groundwater and surface water results confirm that isotopes and MST analyses were complementary and provided more reliable information on the source of nitrate contamination. The isotope and MST data agreed or partially agreed in most of the samples evaluated (79 %). This approach was especially useful for nitrate pollution tracing in surface water but was also effective in groundwater samples influenced by organic nitrate pollution. Furthermore, the findings from the WWTP effluents suggest that the use of literature values to define the isotopic ranges of anthropogenic sources can constrain interpretations. We therefore recommend that local sources be isotopically characterized for accurate interpretations. For instance, the detection of MST inferred animal influence in some WWTP effluents, but the ẟ 11 B values were higher than those reported in the literature for wastewater. The results of this study have been used by local water authorities to review uncertain cases and identify new vulnerable zones in Catalonia according to the European Nitrate Directive (91/676/CEE). Graphical abstract: Image, graphical abstract